The Wiley handbook of social studies research - Manfra, Meghan McGlinn; Bolick, Cheryl Mason (Malden, Massachussetts Wiley-Blackwell, 2017)
"The Wiley Handbook of Social Studies Research is a wide-ranging resource on the current state of social studies education. This timely work not only reflects on the many recent developments in the field, but also explores emerging trends. This is the first major reference work on social studies education and research in a decade. An in-depth look at the current state of social studies education and emerging trends. Three sections cover: foundations of social studies research, theoretical and methodological frameworks guiding social studies research, and current trends and research related to teaching and learning social studies. A state-of-the-art guide for both graduate students and established researchers. Guided by an advisory board of well-respected scholars in social studies education research"--
Contents: 1: Introduction to the Wiley Handbook of Social Studies Research; 2: A Concise Historiography of the Social Studies; 3: The Intellectual History of the Social Studies; 4: Quantitative Research and Large-Scale Secondary Analysis in Social Studies; 5: Qualitative Inquiry in Social Studies Research; 6: Practitioner Research in the Social Studies: Findings from Action Research and Self-Study; 7: Exemplars from the Field of Social Studies Education Research; 8: Critical Theory(s); 9: A Critical Race Theory Analysis of Social Studies Research, Theory and Practice; 10: Gender and Feminist Scholarship in Social Studies Research: A Dynamic Theoretical Framework Living on the Edges; 11: Sexuality and Queer Theory in the Social Studies; 12: Social Constructivism and Student Learning in Social Studies; 13: Democratic Citizenship Education: Research Across Multiple Landscapes and Contexts; 14: Teaching and Learning about controversial issues and topics in the social studies: A Review of the Research; 15: Disciplined Inquiry in Social Studies Classrooms; 16: Becoming an "Expert" Social Studies Teacher: What We Know about Teacher Education and Professional Development; 17: Children's Learning and Understanding in their Social World; 18: Leveraging Literacy: Research on Critical Reading in the Social Studies; 19: Emergent Bilinguals in the Social Studies; 20: The Problem of Knowing What Students Know: Classroom-Based and Large-Scale Assessment in Social Studies; 21: Media and Social Studies Education; 22: The Diffusion of Technology into the Social Studies; 23: Global Education; 24: Social Studies Scholarship Past, Present, and Future; Index
UP System perpetual contents
Includes bibliographic references and index
Keywords: Social sciences -- Research -- Handbooks, manuals, etc